Enhancing productivity of rainfed farms by adopting bael + cowpea horti-agri system strengthened with water conservation practices - Sudhishri, Susama; Singh, Man; Dass, Anchal; A S, Naqibullah; Usha, K. (Indian Farming, 2018)
Rainfed agriculture constitutes thesource of food and livelihood securityof millions of people worldwide.However, production of rainfed areasis constrained by the extremevariability in rainfall, poor nutrientstatus of soils, land degradation through erosion etc. Under suchsituations, horti-agri and otheragroforestry land use systems are thebest options to protect the land fromvarious types of degradation,diversifying the farming system andincreasing the soil carbon build upand moisture storage. These benefitsof agroforestry can be improved byincorporating in-situ moistureconservation practices and legumecrops intercropped with fruit treesmay provide important source of cashand income. In a field experimentcarried out at Research Farm, WaterTechnology Centre, IndianAgricultural Research Institute, NewDelhi during kharif of 2015 and2016 with cowpea grown in bael treeorchard provided with contour trenchon its upper side of bael tree rows forwater conservation, inclusion ofcowpea enhanced the bael fruit yieldand also the total yield (bael +cowpea) expressed as cowpea greenpodequivalent yield, when the plotswere provided with contour trenchtreatment for water conservation.The study demonstrated that bael treeor any other hardy horticultureintercropped with cowpea and thesystem supported with contourtrench water conservation practice inthe upstream of tree can immenselyincrease farm productivity andincome under rainfed conditions ofarid and semi-arid climate.